Global Dominance in Crude Palm Oil (CPO): Strategic Factors Shaping Indonesia's Competitive Edge-A Panel Data Approach - Pratama, Kenny Pradipta Montoya Putra; Sukmawati, Cindy Putri; Abidin, Ali Zainal (National Research and Innovation Agency, 2024)
As a dominant player in the global Crude Palm Oil (CPO) industry, Indonesia requires strategies to sustain its competitive advantage. This research aims to analyze the strategic factors influencing the competitiveness of Indonesia's CPO in the international market, using the Revealed Comparative Advantage (RCA) method and panel data regression analysis through the Generalized Method of Moments (GMM) approach. The findings indicate that Indonesia's comparative advantage in CPO is significantly influenced by global economic dynamics, importers' policies, increasingly stringent environmental regulations, and intensifying global competition. Additionally, the regression results reveal that economic growth, exchange rates, the population of importing countries, and global CPO prices positively impact the competitiveness of Indonesia's CPO in the international markets. In contrast, inflation in importing countries has a negative effect. Therefore, the government must formulate adaptive policies to address global challenges, capitalize on international opportunities through economic diplomacy, maintain macroeconomic stability, improve CPO production quality, and strengthen competitiveness through technological innovation and supply chain efficiency. These steps are crucial to maintaining Indonesia's dominance in the global CPO industry while promoting sustainable economic growth.